Effectiveness Analyses of an Electrospray Sustainer Engine Installed on a Spacecraft Maneuvering in Vicinity of an Asteroid. (2017) - Shornikov, Andrey; Starinova, Olga
Abstract: Motion in vicinity of complex bodies is unstable due to the dynamic changing of the irregular gravitational field. Standard spacecraft power plants designed for interplanetary flights do not provide a stable orbital motion near irregular bodies. In this paper the effectiveness analysis of an electrospray engine power plant used as a sustainer engine in an asteroid exploration mission is considered. Authors describe mathematical models of the spacecraft's motion in an unstable gravitational field as the classical n-body problem. Using simple control schemes for the spacecraft's orbital motion allows basic requirements for the spacecraft's power plant to be defined: thrust level and exhaust velocity. Ion Electrospray Systems are designed to be installed on small satellites, however, effectiveness analyses shows that the characteristics of the calculated engine system is close enough to the characteristics of an electrospray system. Authors demonstrate that ion Electrospray System modules are effective enough to be installed on spacecraft in asteroid exploration missions.